2019
DOI: 10.3389/fpls.2019.00028
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Three (Iso)flavonoid Glucosyltransferases From Pueraria lobata

Abstract: (Iso)flavonoids are one of the largest groups of natural phenolic products conferring great value to the health of plants and humans. Pueraria lobata, a legume, has long been used in Chinese traditional medicine. (Iso)flavonoids mainly present as glycosyl-conjugates and accumulate in P. lobata roots. However, the molecular mechanism underlying the glycosylation processes in (iso)flavonoid biosynthesis are not fully understood. In the current study, three novel UDP-glycosyltransferases (PlUGT4, PlUGT15, and PlU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Recently, three new (iso)flavonoid glycosyltransferases (PlUGT4, −15 and −57) were identified in P. lobate . PlUGT15 and PlUGT57 exhibit much higher isoflavone specificity than other 7-O-UGTs found in P. lobate (Wang X. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recently, three new (iso)flavonoid glycosyltransferases (PlUGT4, −15 and −57) were identified in P. lobate . PlUGT15 and PlUGT57 exhibit much higher isoflavone specificity than other 7-O-UGTs found in P. lobate (Wang X. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 87%
“…In plants, glycosylation is a key modification that allows the formation of a myriad of secondary metabolites, which play many important roles in plant responses to challenges faced during growth and development (Bowles et al, 2005 ; Gachon et al, 2005 ; Campos et al, 2019 ). PlUGT4, −15 and −57 are up-regulated in P. lobata roots after methyl jasmonate treatments (Wang X. et al, 2019 ), and PlUGT1 may be related to the defense response against the MeJA treatment. In this paper, all the BcUGTs were up-regulated after CuCl 2 stress, especially BcUGT1 and BcUGT2, which have highly homologous nucleotide sequences and broad substrate ranges.…”
Section: Discussionmentioning
confidence: 99%
“…However, enzymes encoded by UGT genes identified as catalyzing the final glycosylation steps in flavonoid biosynthesis were rare, and remained to be fully characterized. Members of the UGT71/72/73/75/78/79/83/91/94 families have been identified in flavonoid biosynthesis pathways in a range of plants [ 18 , 20 , 46 - 49 ]. In this study, we investigated the involvement of NtUGT genes in flavonoid biosynthesis in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…13 ). This suggested that the P. thomsonii genome had undergone extensive chromosome rearrangement despite its estimated more recent WGD compared with G. max , which coincided with the smaller number of chromosomes in P. thomsonii [ 15 ].…”
Section: Discussionmentioning
confidence: 99%